Development and Validation of a YUWA JOSH Questionnaire among Youth of Dehradun, Uttarakhand, India - Kumar, Santosh; Ekta, Pathak; Singh , Bhawana (Indian Journal of Community Health, 2025)
Background: Youth (15–24 years) represent a vital demographic facing multifaceted challenges affecting holistic wellness. Existing tools have limited cultural adaptation for Indian youth and often lack comprehensive multidimensional approach. AIM : This study aims to develop and validate the YUWA JOSH Questionnaire (Version 1.0), a culturally relevant instrument assessing holistic wellness among youth of Dehradun, Uttarakhand, India. Methods: The Questionnaire was developed based on multidimensional wellness framework adapted for the Indian context through expert consultation. The initial 38-item questionnaire underwent content validation by a panel of experts in psychology, public health, and education. Data were collected from 283 youth aged 15–24 years from schools and colleges. “Exploratory factor analysis (EFA) with principal axis factoring and oblimin rotation” identified the underlying factor structure. Internal consistency was assessed by “Cronbach’s alpha”. “Confirmatory factor analysis (CFA)” evaluated model fit. Results: EFA revealed a four-factor solution accounting for 39.4% of the total variance, representing Interpersonal ,Academic Pressure and Psychological distress, Emotional Distress, Substance Use Behaviors, and Sleep & Physical Exercise domains. Cronbach’s alpha values ranged from 0.59 to 0.86 across factors, indicating acceptable to good reliability. CFA demonstrated good model fit on the RMSEA index (0.055, 90% CI: 0.048–0.062), though CFI (0.86) and TLI (0.845) suggested potential areas for refinement. Conclusion: The YUWA JOSH (Youth Upliftment and Awareness: Journey Towards Optimism, Strength and Harmony) questionnaire is a reliable multidimensional instrument capturing key domains relevant to Indian youth. Building upon this foundational work, the authors plan to incorporate Financial Wellness domain and conduct subsequent validation studies to enhance the questionnaire’s scope and psychometric robustness.